The repercussions of your cell phone on your heart- The current evidence and the future - Anamika, FNU; Sawhney, Aanchal; Singh, Sandeep; Kohli, Aditya; Kanagala, Sai Gautham; Gupta, Vasu; Garg, Nikita; Jain, Rohit (Eastern Journal of Medical Sciences, 2025)
The use of mobile phones has become widespread in recent years, with many individuals using them for extended periods daily. With the advancements in technology, smartphones have been equipped with features to aid in monitoring heart rate, blood pressure, and even recording ECGs. However, there is also a potential concern regarding its negative effects on heart rate, blood pressure, and heart rhythm, and it may elevate the chances of arrhythmias in individuals with pre-existing heart conditions. While the convenience and connectivity provided by mobile phones are undeniable, there are concerns about their potential impact on cardiovascular health. Current studies suggest the cardiovascular effects of electromagnetic waves, but they only look at the short-term effects of mobile phone usage. This paper aims to discuss the impact of using cell phones on cardiovascular health.